Financial Control Further Improves the Financial Performance of MSMEs Towards Going International - Djoewita, Djoewita; Sudarmiatin, Sudarmiatin; Handayati, Puji (International Journal of Business, Law, and Education, 2025)
This study examines financial literacy and technology's effect on the financial performance of Micro, Small, and Medium Enterprises (MSMEs), with financial control as a moderating variable. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 364 MSMEs in Malang City, Batu City, and Malang Regency that target international markets from January to March 2025. The findings reveal that financial literacy, financial technology, and financial control significantly influence the financial performance of MSMEs. Notably, financial control strengthens the relationship between financial literacy and financial performance, but it does not moderate the effect of financial technology on financial performance. These results suggest that while both financial literacy and financial technology are critical for MSME growth, their effectiveness is enhanced when supported by robust financial control systems. The study recommends that MSMEs prioritize building strong financial control mechanisms from the early stages of business operations to maximize the benefits of financial literacy and technology adoption. In addition, as digital transaction methods continue to evolve, MSMEs must select and utilize appropriate financial technologies to improve service delivery and competitiveness in international markets. This research contributes to the growing body of literature on MSME development by providing empirical evidence of the moderating role of financial control and emphasizing the strategic alignment between financial literacy, control, and technology to drive financial performance and international readiness.